PENGGUNAAN GAYA EKSPOSITORI DALAM PRODUKSI FILM DOKUMENTER “MANTRA SARIRA“ - Angelica, Gabriela; Bumiarta, Made Rai Budaya; Lawranta, Gangga (CALACCITRA: JURNAL FILM DAN TELEVISI, 2025)
Mantra Sarira is a documentary film that explores body painting as a reflection of the dynamic interplay between tradition and modernity in Balinese culture. Through the creative journey of body painting artists, the film examines two main dimensions: the sacred Ngerebeg ritual in Tegallalang, deeply rooted in spiritual values, and modern body painting as a medium for self-expression and contemporary aesthetics. Using an expository approach, the documentary presents a rich visual narrative, indepth interviews with artists, and authentic documentation of the creative process. This study reveals that body painting not only preserves cultural heritage but also transforms into an innovative part of the contemporary art industry, offering both economic and creative opportunities. The findings suggest that body painting serves as a bridge between two worlds—traditional and modern—by combining symbolic meaning with artistic freedom. This research aims to contribute to the understanding of contemporary art development in Indonesia, strengthen appreciation for traditional arts, and inspire younger generations to merge personal creativity with deep cultural roots.